Strategies for Implementing Character Education through Islamic Education at MAN 10 Jombang - Husna, Asiyah Lu'Lu'ul; Hidayah, Nurul; Rivan, Achmad (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Religious education is one of three subjects that must be included in the curriculum of every formal educational institution in Indonesia. This is because religious life is one dimension of life that is expected to be realized in an integrated manner. Character education is a system of instilling good character values in all those involved and as school members so that they have knowledge, awareness and action in implementing these values. The approach used in this research is a qualitative approach, namely a research procedure that produces two descriptives in the form of speech or writing and behavior that can be observed from the subject itself. This type of research is descriptive, namely research that describes information data based on facts obtained in the field. The results of this research are answers to the problem formulation previously determined through observations, interviews and documentation carried out by researchers. The following are the results of interviews conducted by researchers at MAN 10 Jombang. Character education is a system of instilling character values which is good for all those involved and as school members so that they have knowledge, awareness and action in implementing these values. From this definition there are three important thoughts, namely: a. Value Transformation Process b. Developed in the mind c. Become one in behavior.